ANALYSIS OF FINANCIAL REPORTING TO IDENTIFY THE ALTERATIONS IN THE EVIDENCE OF A INTANGIBLE ASSETS BECAUSE OF LAW 11.638/07 - Igarashi, Deisy Cristina Corrêa (2011)
With the internationalization of accounting standards, in Brazil was promulgated the law n° 11. 638/07 that created the intangible group in asset of balance sheet. This study has for objective to analyze alterations in evidencing form of intangible assets, based on financial statements of 10 companies with greater social capital disclosed by BM&FBOVESPA in2010, incomparison to evidenced elements before law 11.638/07. For development of study some methodological procedures were used, standing out the content analysis, which was accomplished in financial demonstratives: Balance Sheet, Notes to the Financial Statements and Management Report. As result was observed: (a) the "A" and "I" companies have the largest variety of intangible evidenced in demonstratives; (b) the intangible types more evidenced in period were "Franchise and licenses", Software" and "Agio for expectation about future profitability"; and (c) "Marks" were the intangible more evidenced implicitly in administration reports of entities in study.ive an) hMas theoretical and conceptual inductive logic. The study is also documentary and adopts the technique of content analysis. As main results: (i) in the national context, there is the empirical relative to theoretical, with more than 95.0% of the work from the perspective of Disclosure and 90.0% in the financial perspective are empirical (ii) identified that in the national strategic perspective with models for measuring and managing intellectual capital as well as multicriteria methodologies, while the international context, the Strategic perspective, there was the adoption of models based on resource and concept (RBV), knowledge-based (KBV), balance sheets or frameworks - Balanced Scorecard (BSC) and specific models of intellectual capital (IC), (iii) as to economic segments stand out in the national focus on education with 13 jobs (9.8%). In the international context, the segments: Financial, Banking, Industrial, and High Technology Companies were mostly received attention in relation to empirical studies, representing in this sense, more than 10.0% of the studies identified. We conclude that the theoretical discussions are relevant or related to the definitions suggested by Marr (2005) proposed the ten prospects in both contexts.